Tanggapan sokongan organisasi, kepuasan kerja, komitmen dan kelakuan kewargaan organisasi pekerja: peranan politik organisasi sebagai perantara - Rasidah Arshad; Suryati Ahmad Zawawi (Penerbit Universiti Kebangsaan Malaysia, 2010)
The study was conducted to investigate direct relationships between perceived organisational support and employees attitudes and behaviour, and indirect relationships via perceived organisational politics. Sample for the study were 176 employees from an organisation in Malaysia. Hypotheses were tested using Structural Equation Modeling. Consistent with past studies, perceived organisational support was negatively related to perceived organizational politics. Significant positive relationships were also found between perceived organisational support and job satisfaction, affective commitment and organisational citizenship behaviour. For the mediating relationship, the only relationship found to be significant was between perceived organisational support and affective commitment